2020
DOI: 10.3390/su12104313
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment of Using Recycled Aggregates in Concrete Block Pavements

Abstract: The mechanistic design of a concrete block pavement (CBP) can be very complicated and often requires the use of computer programs. This paper presents a new mechanistic-empirical method, which is implemented in a computer program (DesignPave) that calculates base course/sub-base thicknesses for a range of design inputs such as traffic load, interlocking properties, and material stiffness. A range of virgin and recycled unbound granular materials were also experimentally tested to characterize them for possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
0
16
0
2
Order By: Relevance
“…Thornthwaite [36] initially applied TMI as a tool to map the climate zones of the United States of America, which was further extended in applications in the agricultural field as an indicator of suitable climates for various crop types [48]. TMI has also been used in other areas, including ecological community, prediction of water catchment capacities and forest growth, and estimation of potential soil suction beneath covered areas and pavements [49][50][51]. In Australia, TMI has been adopted to understand general differences in climate across the country [49,52] and estimate the depth of design soil suction changes H s, which is needed to determine y s [42].…”
Section: Methods For Estimating Tmimentioning
confidence: 99%
“…Thornthwaite [36] initially applied TMI as a tool to map the climate zones of the United States of America, which was further extended in applications in the agricultural field as an indicator of suitable climates for various crop types [48]. TMI has also been used in other areas, including ecological community, prediction of water catchment capacities and forest growth, and estimation of potential soil suction beneath covered areas and pavements [49][50][51]. In Australia, TMI has been adopted to understand general differences in climate across the country [49,52] and estimate the depth of design soil suction changes H s, which is needed to determine y s [42].…”
Section: Methods For Estimating Tmimentioning
confidence: 99%
“…In general, CBP consists of a layer of rigid blocks laid on top of a sand or gravel bedding course underlain by granular or other materials depending on traffic conditions and the mechanical properties of the subgrade. CBPs are often treated as flexible pavement and are commonly used in road or industrial applications [169]. Common configurations of CBPs are presented in Figure 19.…”
Section: Sustainability Analysismentioning
confidence: 99%
“…A wide range of costs has been reported in the literature. For example, Ivanov and Chu [26] estimated the material cost for MICP to be as low as $5/m 3 of treated soil; while Esnault-Filet et al [169] estimated the cost of materials, labour and equipment to be as high as $500/m 3 of treated soil. In this section, a quantitative sustainability assessment has been conducted for a simplified hypothetical engineering construction scenario.…”
Section: Sustainability Analysismentioning
confidence: 99%
“…Often, RA have been used for concrete block pavements [10,11], but other research [9,[12][13][14] has shown how it is possible to produce structural concrete with RA. Limbachiya et al [14] found that flexural strength and modulus of elasticity of concrete containing recycled aggregates are similar to the ones of concrete made with NA.…”
Section: Introductionmentioning
confidence: 99%